A simulated colorimetric INHIBIT logic gate based on 2-(2-thiazolylazo)-p-cresol. Issue 8 (13th September 2016) - Liu, Hai-Bo; Zhao, Hong-Yi; Wang, Jing
ABSTRACT: 2-(2-Thiazolylazo)- p -cresol system achieved distinct optical output signal by controlling pH and mercury-ion complexation. The 2-(2-thiazolylazo)- p -cresol with mercury ion existed as an equilibrium mixture of both an azo and hydrazone tautomeric forms at 372 and 425 nm, respectively, along with the appearance of a new absorption peak at 610 nm (visual color of green), which was attributed to the binding of mercury ion with 2-(2-thiazolylazo)- p -cresol. Furthermore, the addition of proton led to the perturbation of the conjugation between 2-(2-thiazolylazo)- p -cresol and mercury ion and absence of absorption at 610 nm (visual color of yellow). 2-(2-thiazolylazo)- p -cresol could thus be applied to develop an effective simulated colorimetric INHIBIT logic gate with mercury ion and proton as inputs. Consequently, green color with the absorption peak at 610 nm was outputted from yellow color of 2-(2-thiazolylazo)- p -cresol in the presence of mercury ion as an input signal at pH 7.0.